Analisis Peran Guru Bimbingan dan Konseling dalam Mendukung Penyelenggaraan SPMB Bagi Siswa Berkebutuhan Khusus Melalui Pendekatan Manajemen BK Berbasis Kolaborasi - Ramdani ramdani; Raja Zulfikar; Rike Ernawati Sinaga (TANJAK, 2026)
The implementation of an inclusive Student Admission System (SPMB) requires the involvement of various stakeholders, including school counselors, to ensure equal educational access for students with special needs. However, the admission process continues to face challenges related to stakeholder coordination, support systems, and school readiness. This study aimed to analyze the role of school counselors in supporting the implementation of SPMB for students with special needs through collaborative guidance and counseling management in secondary schools. The study employed a quantitative approach with a descriptive-comparative survey design. Participants consisted of 19 school counselors from five secondary schools in Batam City, including two senior high schools, one Islamic senior high school, and two vocational high schools. Total sampling was applied. Data were collected using a questionnaire measuring four dimensions: counselors’ understanding, counselors’ roles, available support, and obstacles encountered in implementing SPMB for students with special needs. Data were analyzed using descriptive statistics and the Kruskal Wallis test. The findings revealed that counselors’ understanding of SPMB for students with special needs was categorized as high (M = 4.08), as was their role in supporting the implementation of SPMB (M = 3.95). The level of support received by counselors was categorized as moderate (M = 3.42), while the obstacles encountered were categorized as high (M = 3.79). Major obstacles included limited competence in handling students with special needs, insufficient preliminary information about prospective students, limited access to professional support services, and suboptimal coordination among stakeholders. Comparative analysis indicated no significant differences in understanding, roles, and support across school types; however, significant differences were found in the obstacle dimension. The findings suggest that the primary challenge in implementing SPMB for students with special needs lies not in counselors’ understanding or roles, but rather in the inadequacy of support systems and collaborative mechanisms. Therefore, the development of a collaborative guidance and counseling management model is needed to integrate multiple stakeholders in supporting a more inclusive student admission process.